Population genetic structure and demographic history of Dermacentor marginatus Sulzer, 1776 in Anatolia - Ömer Orkun; Eneshan Sarıkaya; Anıl Yılmaz; Mesut Yiğit; Zati Vatansever (Scientific Reports)
Abstract Dermacentor marginatus is a medically important tick species due to its preference humans and domestic animals as hosts and its vectorial competence, yet it remains understudied in many regions. This study aimed to examine the population structure and demographic history of D. marginatus using the cox1 and ITS2 genes, focusing on populations from Central and Northeast Anatolia—two regions on either side of the Anatolian Diagonal, a natural biogeographical barrier. A total of 361 host-seeking adult D. marginatus ticks from 31 sampling sites were analyzed, revealing 131 haplotypes for cox1 and 104 genotypes for ITS2. Neutrality tests and mismatch distribution patterns rejected the null hypothesis of the neutral theory, indicating that the population of D. marginatus in Anatolia has undergone a recent demographic expansion. Significant genetic differentiation and population structuring were observed between the Central and Northeastern Anatolian populations of D. marginatus, correlating with geographic distance and suggesting that the Anatolian Diagonal acts as a potential barrier to gene flow. Intrapopulation gene flow was higher in Central Anatolian populations compared to Northeastern Anatolian populations. Bayesian phylogeny revealed a highly divergent D. marginatus haplotype within the Northeastern Anatolian population, clustering into a Central Asian clade. Additionally, phylogenetic trees of the subgenus Serdjukovia revealed taxonomic ambiguities, including the absence of a distinct clade for D. niveus and potential misidentifications of D. marginatus and D. raskemensis specimens. Furthermore, the monophyletic relationship between D. marginatus and D. raskemensis supports the likelihood of sympatric speciation. These findings enhance our understanding of the genetic structure, phylogeography, and evolutionary dynamics of D. marginatus while providing a framework for future research on tick populations.